Sciaphila secundiflora Thwaites ex Benth. (Triuridaceae), a new record for Thailand - Triboun, Pramote; Larsen, Kai (Thai Forest Bulletin (Botany), 2014)
Sciaphila secundiflora, a new record for Thailand, is described and illustrated .